2014
DOI: 10.1080/19361653.2014.878564
|View full text |Cite
|
Sign up to set email alerts
|

The Success of Gay–Straight Alliances in Waterloo Region, Ontario: A Confluence of Political and Social Factors

Abstract: This paper outlines how gay-straight alliances (GSAs) work to connect youth with community resources, and outlines the political and social context of GSAs in Waterloo Region, Ontario, Canada. Fifteen individuals (youth, teachers and service providers) participated in interviews about the role of GSAs in creating supportive school environments for LGBTQ youth. Apart from providing direct support to LGBTQ students, GSAs in Waterloo Region decrease isolation by connecting youth with other LGBTQ community members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Secondly, we hypothesized that GSA presence would be associated with greater school engagement, as a number of previous studies have suggested that having a GSA at school relates to school belonging, decreased isolation, greater ability to identify safe adults, increased comfort and openness, and increased engagement for LGBTQ students (Fischer, 2011;Garcia-Alonso, 2004;Heck, Flentje, et al, 2013;Quasha, 2011;St. John et al, 2014;Toomey et al, 2012;Walls et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we hypothesized that GSA presence would be associated with greater school engagement, as a number of previous studies have suggested that having a GSA at school relates to school belonging, decreased isolation, greater ability to identify safe adults, increased comfort and openness, and increased engagement for LGBTQ students (Fischer, 2011;Garcia-Alonso, 2004;Heck, Flentje, et al, 2013;Quasha, 2011;St. John et al, 2014;Toomey et al, 2012;Walls et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of Poteat et al (2013) and Diaz et al (2010), most scholarship has confirmed a relationship between GSA presence and connections to school, whether measured as school belonging, decreased isolation, ability to identify safe adults, increased comfort and openness, or increased engagement (Fischer, 2011;Garcia-Alonso, 2004;Heck, Flentje, et al, 2013;Quasha, 2011;St. John et al, 2014;Toomey, McGuire, & Russell, 2012;Walls et al, 2010).…”
Section: Gay-straight Alliances and Lgbtq Studentsmentioning
confidence: 99%
“…This strategy was carried out by initiating and maintaining programs that connected their LGBT students with community-based resources created through inter-agency networks. By establishing alliances with LGBT-positive agencies from their immediate outside community, schools were able to provide access to resources to their LGBT students such as external funding, technical expertise, social networking, and materials such as books and videos that catered to their interests and needs (St. John et al, 2014). These extra resources were especially important for LGBT students who were studying in schools located in rural communities (Snively, 2003).…”
Section: Providingmentioning
confidence: 99%
“…In Canada, the educational system differs in the sense that public funding from the government is not only provided to public secular schools but also to Catholic separate schools in certain provinces such as Ontario, Saskatchewan, and Alberta. In this context there have been only a few studies on the success of GSAs and other strategies and programs that support LGBT youth in high schools (Goldstein, Collins, & Halder, 2005St. John et al, 2014).…”
Section: The Canadian Catholic School System Contextmentioning
confidence: 99%
See 1 more Smart Citation